62 Time course of improvement in secretory unbalance of asymmetric dimethylarginine and nitric oxide productions in response to exercise training in middle-aged and older adults. (13th January 2020) - Fujie, S; Hasegawa, N; Sanada, K; Hamaoka, T; Maeda, S; Iemitsu, M
Abstract: Funding Acknowledgements: Supported by Grants-in-Aid for Scientific Research (#17H02182, #16K13059, M. Iemitsu; #18J01024, S. Fujie) Introduction: Aging is well known to elevate risks of cardiovascular diseases. As a mechanism of these increased risks with aging, a reduction of nitric oxide (NO) production via augmented secretion of asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthesis is related. Habitual aerobic exercise has shown to improve secretory unbalance of endothelium-derived regulating factors with aging, such as increase in NO and decrease in ADMA, resulting in the reduction of arterial stiffness. However, the time course of improvement in secretory unbalance of NO and ADMA productions in response to exercise training in middle-aged and older adults remains unclear. Purpose: This study aimed to determine the time course of changes in plasma nitrite/nitrate (NOx) and ADMA levels related to exercise-training effects of arterial stiffness in healthy middle-aged and older adults. Methods: Thirty-two Japanese healthy middle-aged and older subjects (67 ± 1 years) were randomly divided into two groups: exercise intervention and sedentary controls. Subjects in the training group completed 8-week of aerobic exercise training (60-70% peak oxygen uptake [VO2peak] for 45 min, 3 days/week). We evaluated plasma NOx and ADMA concentrations and carotid-femoral pulse wave velocity (cfPWV) as an index of arterial stiffness, measured every 2 weeks for 8-week in the training group. Results: cfPWV was gradually declined from baseline to 8-week and significantly decreased from baseline at weeks 6 (P < 0.05) and 8 (P < 0.01). Plasma NOx level was gradually elevated during exercise intervention and significantly increased from baseline at weeks 6 (P < 0.05) and 8 (P < 0.01). Interestingly, plasma ADMA level was significantly decreased at 8-week intervention (P < 0.05). Furthermore, the exercise training-induced reduction in plasma ADMA level was negatively correlated with the change in plasma NOx level before and after the 8-week (r = -0.483, P < 0.05). The exercise training-induced change in plasma ADMA concentration was positively correlated with training-induced change in cfPWV before and after the 8-week (r = 0.633, P < 0.01). Additionally, there was a negative correlation between the changes in plasma NOx level and cfPWV before and after the 8-week (r = -0.642, P < 0.05). Conclusions: These results suggest that habitual aerobic exercise can normalize the secretory unbalance of NO and ADMA productions in 6 to 8 weeks, and these balance normalizations may be contributed to the reduction of arterial stiffness in the middle-aged and older adults.